Monitoring dan Kontrol Pemberian Pakan Air Tawar Menggunakan Internet Messaging Secara Real time - Yakobus Dapi; Ikhwan Ruslianto; Suhardi Suhardi (Universitas Budi Darma, 2022)
One important aspect that must be considered in freshwater aquaculture is the feeding of the fish. However, in its implementation, fish feeding is generally still done conventionally, farmers must sprinkle feed every day with an irregular amount of feed and time. The next problem is the limitations of humans as fish farmers to carry out several activities at the same time and in separate places. Therefore, a system was created that can monitor and control the feeding of fish in real time using Internet Messaging based on the Internet of Things via Telegram. NodeMCU ESP32 is used as overall system control. The hardware used to open and close the fish feed gap is a Tower Pro Micro Servo 9g SG90 360 Continuous type servo motor. The HC-SR04 Ultrasonic Sensor Device is used to determine the remaining feed in the storage container when the feed execution is complete. The test results showed that fish feeding was successfully carried out with the average weight of automatic feeding scheduled every 07.01 WIB and 16.01 WIB was 4 grams, and 6.17 grams for manual feeding. Detection of residual fish feed was also successfully carried out with an average error value of 27.74%. Then, the average response time during execution of opening the feed gap is 3.36 seconds and 3.46 seconds to close the feed gap.